Analisis Manajemen Pemerataan Sistem Pendidikan di Kota Tangerang Selatan sebagai Upaya Pencegahan Kasus Korupsi - Khanaya; Setiawan, Jeanne Evelina; Azka, Ladya; Ardena, Syifa; Yesisca, Leoni (PT. Lancar Media Komunikasi, 2025)
Equal distribution of education in the city of South Tangerang is an issue that requires special attention, which must be resolved immediately as an effort to improve the quality of Human Resources (HR). Educational equality is an effort to ensure that every individual has the same opportunity to gain access to and adequate quality of education. However, when the issue of corruption arises in the context of educational equality, this shows that resources that should be used to improve access and quality of education are often misused for personal gain or that of a particular group. This research aims to create a systematic, factually accurate picture and the rela-tionship between the phenomena that occur. The data obtained during this research will be pro-cessed and further processed using existing theories. In this research, we used qualitative methods in the form of descriptive data supported by journals and information from official websites. From the research that has been carried out, it can be concluded that the distribution of the education system in the city of South Tangerang is not yet completely equal. The lack of equal distribution of education in the city of South Tangerang can have an impact on the quality of education and the quality of education for all students